2015
DOI: 10.1142/s2377740015500323
|View full text |Cite
|
Sign up to set email alerts
|

China’s Pursuit of a New Asia-Pacific Security Architecture

Abstract: Facing increasing challenges to regional peace and stability, yet feeling isolated in several key security mechanisms in the Asia-Pacific, China has been taking active measures to improve its security environment and to foster a new regional security architecture based on the “New Asian Security Concept,” in order to achieve a lasting and commonly beneficial collective security order in the region. Though no official blueprint has been established by the Chinese government, one can expect China to push forward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The structures of the isolates were established by analysis of the extensive spectroscopic data (such as HR-ESI-MS, 1D/2D NMR, ORD, and ECD). Among them, compound 1 represents a previously undescribed furfural derivative, and the other twentyfive known compounds (2-26) were identified as 1,4-difuranyl-2,3dihydroxy-1,4-butanedione (2), [8] tuberostemonoxonine (3), [9] didehydrotuberostemonine A (4), [10] N-(4-hydroxyphenethyl)acetamide (5), [11] aurantiamide (6), [12] aurantiamide acetate (7), [13] stilbostemin B 3'-O-β-D-glucopyranoside (8), [14] trans-resveratrol 3-O-β-D-glucopyranoside (9), [15] daidzin (10), [16] rutin (11), [17] emodin-8-O-β-Dglucopyranoside (12), [18] psoralen (13), [19] isopsoralen ( 14), [20] isoacteoside (15), [21] 3,5-dihydroxy-1-(3,4-dihydroxyphenyl)-7-(4hydroxyphenyl)heptane ( 16), [22] (+)-syringaresinol (17), [23] (+)-syringaresinol-4-O-β-D-glucoside (18), [24] hydroxybenzaldehyde (19), [25] 3-hydroxy-4-methoxybenzoic acid (20), [26] 4-methoxybenzoic acid (21), [27] 4-hydroxybenzonic acid ( 22), [28] 1,2,4-benzenetriol (23), [29] caffeic acid (24), [17] 4-hydroxycinnamic acid (25), [30] and protocatechuic acid (26), [31] Analysis of the 1D NMR, HMQC, and HMBC data allowed the overall assignments of the NMR data of 1 as listed in Table 1. Further, NOESY correlations between H 3 -11 and H-2/H-5/H-7, and between H-5 and H-7, indicated that H-2, H 3 -11, H-5, and H-7 were at a relatively close distance in space, or oriented in the same direction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The structures of the isolates were established by analysis of the extensive spectroscopic data (such as HR-ESI-MS, 1D/2D NMR, ORD, and ECD). Among them, compound 1 represents a previously undescribed furfural derivative, and the other twentyfive known compounds (2-26) were identified as 1,4-difuranyl-2,3dihydroxy-1,4-butanedione (2), [8] tuberostemonoxonine (3), [9] didehydrotuberostemonine A (4), [10] N-(4-hydroxyphenethyl)acetamide (5), [11] aurantiamide (6), [12] aurantiamide acetate (7), [13] stilbostemin B 3'-O-β-D-glucopyranoside (8), [14] trans-resveratrol 3-O-β-D-glucopyranoside (9), [15] daidzin (10), [16] rutin (11), [17] emodin-8-O-β-Dglucopyranoside (12), [18] psoralen (13), [19] isopsoralen ( 14), [20] isoacteoside (15), [21] 3,5-dihydroxy-1-(3,4-dihydroxyphenyl)-7-(4hydroxyphenyl)heptane ( 16), [22] (+)-syringaresinol (17), [23] (+)-syringaresinol-4-O-β-D-glucoside (18), [24] hydroxybenzaldehyde (19), [25] 3-hydroxy-4-methoxybenzoic acid (20), [26] 4-methoxybenzoic acid (21), [27] 4-hydroxybenzonic acid ( 22), [28] 1,2,4-benzenetriol (23), [29] caffeic acid (24), [17] 4-hydroxycinnamic acid (25), [30] and protocatechuic acid (26), [31] Analysis of the 1D NMR, HMQC, and HMBC data allowed the overall assignments of the NMR data of 1 as listed in Table 1. Further, NOESY correlations between H 3 -11 and H-2/H-5/H-7, and between H-5 and H-7, indicated that H-2, H 3 -11, H-5, and H-7 were at a relatively close distance in space, or oriented in the same direction.…”
Section: Resultsmentioning
confidence: 99%
“…Among the above twenty-six compounds, compounds 1 and 2 are two rare di-furfural derivatives, compound 1 represents a previously undescribed one featuring a furanolac- tone ring, and compound 2 has been reported previously only from Rhizoctonia solani, [39] and processed Polygonatum cyrtonema Hua., [8] with anti-inflammatory potential by inhibiting NO release in LPS-induced RAW264. [14,26,[33][34][35][36] As reported to date, tuberostemonoxonine (3), [37,38] didehydrotuberostemonine A (4), [10] stilbostemin B 3'-β-D-glucopyranoside (8), [14] and rutin (11) [39] have been isolated only from S. tuberosa among the three species [S. tuberosa Lour., S. sessilifolia (Miq.) Miq., and S. japonica (Blume) Miq.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This framework is then rooted in China's antipathy for military alliances which, according to its diplomats and top officials, are 'unnecessary vestiges of the Cold War' (Shambaugh, 2004: 70). However, NASC was followed by confusing rhetoric and behaviour and no breakthroughs have been achieved since its proposal (Zhang, 2015). Two years later, it was de facto shelved.…”
mentioning
confidence: 99%